2021
DOI: 10.1096/fj.202100161r
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐based limits to running speed in the human, horse and dog: The role of sexual dimorphisms

Abstract: Among humans, males have faster running performances than females ubiquitously across all race distances despite faster improvements in record times for females compared to males over the previous century. 1-3 Strikingly, however, these sex differences in elite running performance may be blunted or nonexistent in other species that engage in competitive running performances, notably the thoroughbred horse and greyhound dog. In this context, elite running performances across species offer a framework to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 64 publications
(141 reference statements)
0
1
0
Order By: Relevance
“…Then, these statements are contrary to the results presented by Al-Shorepy ( 14 ) for racing camels, Entin ( 87 ) for racehorses and Greyhound dogs, Vicente et al ( 88 ) for classical riding horses, and Navas González et al ( 33 ) for assisted-therapy donkeys, who reported a significant effect of sex and age on animal functional performance but agreed with Senefeld et al ( 89 ), who support the idea that large differences in athletic performance do not exist between sexes in animals. Regarding the association between coat and eye color with different psychological constructs that are transcendental for animal trainability and safe interaction, the molecular basis of these desirable traits has been identified mainly for dogs and horses ( 90 93 ), and some inferences are discussed by Iglesias Pastrana et al ( 77 ) for dromedary camels.…”
Section: Discussionmentioning
confidence: 63%
“…Then, these statements are contrary to the results presented by Al-Shorepy ( 14 ) for racing camels, Entin ( 87 ) for racehorses and Greyhound dogs, Vicente et al ( 88 ) for classical riding horses, and Navas González et al ( 33 ) for assisted-therapy donkeys, who reported a significant effect of sex and age on animal functional performance but agreed with Senefeld et al ( 89 ), who support the idea that large differences in athletic performance do not exist between sexes in animals. Regarding the association between coat and eye color with different psychological constructs that are transcendental for animal trainability and safe interaction, the molecular basis of these desirable traits has been identified mainly for dogs and horses ( 90 93 ), and some inferences are discussed by Iglesias Pastrana et al ( 77 ) for dromedary camels.…”
Section: Discussionmentioning
confidence: 63%